Air ingress analysis of chimney effect in the 200 MWe pebble-bed modular high temperature gas-cooled reactor. (August 2017) - Chen, Zhipeng; Chen, Xiaoming; Zheng, Yanhua; Sun, Jun; Chen, Fubing; Shi, Lei; Li, Fu; Dong, Yujie; Zhang, Zuoyi
Highlights: HTR is a candidate for the Generation IV nuclear energy system technology with well-known inherent safety features. Air ingress accident receives high attention. The air ingress accident of HTR-PM due to chimney effect has been studied. A mitigation measure for air ingress accident has been proposed and evaluated. Abstract: In a high temperature gas-cooled reactor (HTGR), one can postulate simultaneous ruptures of the pressure boundary at points near the top and bottom of the reactor vessel. In this extremely low probability event, depressurization and heat-up of the core can lead to ingress of air into the vessel driven by the buoyancy of the hot helium relative to the colder, cavity air ('chimney effect'). Although this is considered a 'beyond design basis accidents' (BDBA), it receives high attention because it may lead to graphite oxidation of reflectors and fuel elements so as to weaken the structural strength and lessen the ability of the coated particles to retain fission products. A study of the rate and severity of the air ingress and potential for oxidation in the 200 MWe Pebble-bed Modular High Temperature gas-cooled Reactor (HTR-PM) is described in this paper. The TINTE code was used to simulate the air ingress accident caused by the simultaneous rupture of the fuel charging tube and fuel discharging tube. A mitigation measure, the injection of nitrogen into the vessel, has also been proposed and evaluated with the TINTE model. The results indicate that, due to the high flow resistance of the pebble-bed core, the air ingress flow rate is limited. The oxygen content in the reactor cavity is also limited due to the design of the Ventilated Low Pressure Containment (VLPC) that prevents the corrosion of the fuel elements and reflectors by limiting the amount of air that can enter the vessel. The results also indicate that the injection of the nitrogen in a suitable location and with a suitable mass flow rate can effectively prevent significant corrosion of the graphite.